2014
DOI: 10.1016/j.jcrysgro.2014.09.018
|View full text |Cite
|
Sign up to set email alerts
|

The role of ultrasonic treatment in refining the as-cast grain structure during the solidification of an Al–2Cu alloy

Abstract: Abstract. The effect of Ultrasonic Treatment (UT) over selected temperature ranges during cooling and solidification of an Al-2Cu alloy melt on the grain structure and cooling behaviour of the alloy has been investigated using a molybdenum sonotrode introduced without preheating. UT was applied over various temperature ranges before, during and after the nucleation of primary aluminium grains. It was found that ultrasonic grain refinement was achieved only when UT was applied from more than 20 o C above the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
79
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 119 publications
(84 citation statements)
references
References 24 publications
(35 reference statements)
4
79
0
1
Order By: Relevance
“…The influence of ultrasonication on the grain refinement of alloys treated above the liquidus was studied extensively. [27] A systematic study by Wang et al [41] in a noninoculated alloy made clear that ultrasonication in a complete liquid state had a negligible effect on grain refinement, which was substantiated in the present study. Nevertheless, the additional grain refinement was observed when ultrasonication was applied to the liquid metal containing MgAl 2 O 4 or TiB 2 particles.…”
Section: Mechanisms Of Grain Refinementsupporting
confidence: 87%
“…The influence of ultrasonication on the grain refinement of alloys treated above the liquidus was studied extensively. [27] A systematic study by Wang et al [41] in a noninoculated alloy made clear that ultrasonication in a complete liquid state had a negligible effect on grain refinement, which was substantiated in the present study. Nevertheless, the additional grain refinement was observed when ultrasonication was applied to the liquid metal containing MgAl 2 O 4 or TiB 2 particles.…”
Section: Mechanisms Of Grain Refinementsupporting
confidence: 87%
“…[16] From Figure 3 is increasing towards the bulk melt temperature [14] indicating that the application of UST at any temperature above the liquidus temperature may improve the efficiency of the master alloy.…”
Section: Discussionmentioning
confidence: 96%
“…[11] Other studies have shown that UST induces significant refinement when applied during cooling from just above to below the liquidus temperature. [13,14] This study will determine precisely when, during UST, nucleation is promoted and the relative contribution these mechanisms make to the final ascast grain size. Additions of an Al3Ti1B master alloy at concentrations of 50 or 200 ppm Ti were introduced into the molten melt at 740±3°C, which was then stirred and held for 5 minutes before being transferred to the UST platform (details reported in [14] ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations